Evaluation of short chain fatty acids production by potent Lactobacillus cultures: an in vitro study - Makwana, Mitali; Prajapati, JB; Hati, Subrota (Indian Journal of Dairy Science, 2022)
Production of short chain fatty acids (SCFAs) is one of the mechanisms thought to be involved in cure of many GI tract disorders. Present study was undertaken to evaluate the probiotics for its SCFAs production capacity. In the study, we selected several potential probiotics cultures and planned this project to screen the Lactic Acid Bacteria (LAB) based on Short-chain fatty acids (SCFAs) production mainly Butyric acid, Propionic acid and Acetic acid at different time intervals (0, 12 and 24 h) of incubation during fermentation in reconstituted skim milk (RSM) media (in vitro study). SCFAs (acetate, propionate, butyrate) production ability was checked by Lactobacillus cultures. The average content of acetic acid was 1.20 Î¼g/ml at 0 h, which increased to 1.53 and 1.93 Î¼g/ml, respectively after 12 and 24 h of incubation. Cultures M5 and NK9 showed relatively higher amount of acetic acid after 24 h. Overall propionic acid production ranged from 1.44 Î¼g/ml (M10 at 0 h) to 3.42 Î¼g/ml (V3 at 24 h). M5 and M31 produced significantly higher propionic acid than the rest of the cultures. It was observed that butyric acid produced by the cultures M5 (2.09 Î¼g/ml) was highest followed by 09 (2.08 Î¼g/ml) and M31 (2 Î¼g/ml). Out of ten Lactobacillus cultures, five cultures viz. V3 (L. helveticus), M5 (L. fermentum), NK9 (L. casei), M31 (L. rhamnosus) and 09 (L. acidophilus) were selected on the basis of higher SCFAs production for further phase of study.